One to watch eaudiobook A novel. - Stayman-London, Kate (Random House Audio, 2020)
NATIONAL BESTSELLER • Real love . . . as seen on TV. A plus-size bachelorette brings a fresh look to a reality show in this razor-sharp, “divinely witty” ( Entertainment Weekly ) debut. “Effortlessly fun and clever . . . I found the tension impeccable . . . and that made my reading experience incredibly propulsive. Read it in a day and a half.”—Emily Henry, #1 bestselling author of Beach Read and The People We Meet on Vacation NAMED ONE OF THE BEST BOOKS OF THE YEAR BY Time • NPR • Marie Claire • Mashable Bea Schumacher is a devastatingly stylish plus-size fashion blogger who has amazing friends, a devoted family, legions of Insta followers—and a massively broken heart. Like the rest of America, Bea indulges in her weekly obsession: the hit reality show Main Squeeze . The fantasy dates! The kiss-off rejections! The surprising amount of guys named Chad! But Bea is sick and tired of the lack of body diversity on the show. Since when is being a size zero a prerequisite for getting engaged on television? Just when Bea has sworn off dating altogether, she gets an intriguing call: Main Squeeze wants her to be its next star, surrounded by men vying for her affections. Bea agrees, on one condition—under no circumstances will she actually fall in love. She’s in this to supercharge her career, subvert harmful beauty standards, inspire women across America, and get a free hot air balloon ride. That’s it. But when the cameras start rolling, Bea realizes things are more complicated than she anticipated. She’s in a whirlwind of sumptuous couture, Internet culture wars, sexy suitors, and an opportunity (or two, or five) to find messy, real-life love in the midst of a made-for-TV fairy tale. In this joyful, wickedly observant debut, Bea has to decide whether it might just be worth trusting these men—and herself—for a chance to live happily ever after.